New host and locality records for Tetrameres (Gynaecophila) spirospiculum Pinto & Vicente, 1995 (Nematoda: tetrameridae), with new morphological data - Digiani, María Celina (2001)
We report the finding of Tetrameres spirospiculum Pinto & Vicente, 1995 from Theristicus melanopis melanopis (Threskiornithidae) from Patagonia, Argentina. These constitute new host and locality records. We propose the assignation of this species to the subgenus T. (Gynaecophila) Gubanov, 1950, based on the presence of labia and the absence of cuticular flanges at the anterior end. Some new morphological data are provided, such as the arrangement of cuticular spines and the presence of a pair of somatic papillae at beginning of posterior third of body length. T. (G.) spirospiculum may probably be regarded as specific to birds of the genus Theristicus.